Tier 3 of the RTI model problem solving through a case study approach - Hunley, Sawyer A.; McNamara, Kathy; Sage eBooks; National Association of School Psychologists (Thousand Oaks, Calif. : Corwin ; London : SAGE [distributor], 2010)
This text offers critical, practical, coherent, comprehensive and research-based information for schools and districts implementing an RTI framework of intervention. It maps a seamless process of support that enables school psychologists and school teams to provide tiered interventions to increase student achievement.
Published in association with the National Association of School Psychologists.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Problem children -- Education -- United States -- Case studies; Remedial teaching -- United States -- Case studies; School failure -- United States -- Prevention -- Case studies; Behavior disorders in children -- Treatment -- United States -- Case studies; Response to intervention (Learning disabled children); Electronic books